Metastatic bone disease (Faculty of Medicine Universitas Indonesia, 2004)
Metastatic bone disease is the most common malignancy of bone, it is estimated that 70% of all malignant bone tumors are metastatic in origin. At autopsy it has been reported between 30 to 85% of patients who die from cancer show occult skeletal metastases. Bone is the third most common site of metastatic process after lung and liver. 80% of metastatic bone disease arise from Ca of breast, prostate, lung, kidney and thyroid. Typical location are thoracolumbal spine, pelvis, ribs, skull and proximal of femur and humerus. Pathogenesis of metastatic bone disease had been explained by Pagetâs âSeed and Soilâ theory and Ewingâs circulatory theory. Diagnostic procedures include complete laboratory examination, diagnostic bone imaging, chest x-ray, total body scan, CT-scan of chest, abdomen and pelvis and confirmed by histopathological examination. Management of metastatic bone disease is palliative that includes : chemotherapy, radiotherapy, bisphosphonates and surgical treatment for impending / established pathologic fracture to alleviate pain, ease nursing and restore functional activity. (Med J Indones 2004; 13: 127-31) Keywords: bone cancer, metastases